Effects of dietary methionine on the growth and protein synthesis of juvenile Chinese mitten crabs (Eriocheir sinensis) fed fish meal-free diets - Jiadai Liu; Erchao Li; Xinyu Li; Xiaodan Wang; Qincheng Huang; Han Wang; Yixin Miao; Qingchao Shi; Jianguang Qin; Liqiao Chen (Animal Nutrition)
This study investigated the effects of dietary methionine (Met) on growth performance and protein synthesis in juvenile Chinese mitten crabs (Eriocheir sinensis) fed fish meal (FM)-free diets. Three diets free of FM containing 0.48% (LM), 1.05% (MM), and 1.72% (HM) Met were assessed, and the cysteine content in all the diets was adjusted to 0.46%. The control diet contained 35% FM without Met supplementation. Extra lysine was added to all of the FM-free diets to match the lysine level in the control diet. Juvenile E. sinensis (800 crabs weighing 0.74 ± 0.01 g each) were fed these four diets for eight weeks, with five replicates for each treatment. Both the LM and HM groups presented lower weight gain than all the other groups did (P = 0.002). The survival of the crabs was lower in the LM and HM groups than in the MM group (P = 0.005). Compared with those in the other groups, the growth performance of the crabs in the MM group improved, and lipid deposition and protein accumulation increased. These positive outcomes are associated with high protein expression linked to the mammalian target of the rapamycin (mTOR) pathway and low expression of genes and proteins linked to the PRKR-like endoplasmic reticulum kinase (PERK) pathway. The study of Met supplementation has explored the response of the PERK pathway through reducing glutathione (GSH) levels to promote protein synthesis. The injection of Met and L-buthionine-sulfoximine (BSO), an inhibitor of GSH synthesis, suppressed GSH production and altered the expression of genes and proteins related to protein synthesis pathways. This study suggests that Met supplementation in FM-free diets can increase the growth and protein synthesis of E. sinensis by modulating specific cellular pathways, particularly the mTOR and PERK pathways.